Credibility at stake. A comparative analysis of different hate speech comments on journalistic credibility and support on climate protection measures - Andreas Schulz-Tomančok; Florian Woschnagg (Cogent Social Sciences)
The contentious nature of certain forms of climate activism has led to a proliferation of hate comments targeting activists in online news forums. This study examines the ‘Nasty Effect’—the impact of uncivil language—on attitudes towards climate protection news. Specifically, we investigate how various types of hate speech within user comments influence the credibility of articles on climate protection and activism. Employing a between-subject design (7x1), we conducted an online survey in Austria during autumn 2023 (N = 486). Our findings reveal that as the hate speech intensity increased, the perceived credibility of related news articles declined. While overall means did not yield significant differences, individual assessments compared to the control group were significant. Explicit hate speech exhibited a more pronounced negative impact on article credibility. The absence of a significant ‘Nasty Effect’ underscores the intricate nature of this phenomenon and its nuanced influence on public attitudes towards climate protection measures.